Leader Driven Organizational Adaptation. Issue 8 (20th August 2014) - Seah, Melody Siew May; Hsieh, Ming-Huei; Huang, Hsiu-Ying
Abstract : Purpose: Earlier research has identified adaptive leadership strategies and organizational culture as two key factors that influence a firm's adaptive capabilities. However, little is known about how leadership and organizational culture affect each other. Nor do we know how the combined effects of adaptive leadership and culture facilitates organizational adaptation over time. This study addresses this gap by using a co-evolutionary perspective to enhance our understanding of this phenomenon. Design/methodology/approach: Data was collected through informant interviews, observations and archival material. Findings: Study findings reveal that leaders can enhance organizational adaptability by creating an appropriate context to guide the co-evolutionary interactions between their leadership strategies, organizational culture and employees towards the ongoing achievement of firm goals. Originality/value: The study enhances our understanding of how leaders facilitate organizational adaptability, especially in a family business context.